A COMPARATIVE STUDY BETWEEN 0.5% LEVOBUPIVACAINE AND 0.75% ROPIVACAINE IN PATIENTS UNDERGOING ELECTIVE LOWER LIMB SURGERIES UNDER SUBARACHNOID BLOCK - DIKKALA, DURGASHEKAR BABU; GUNTREDDY, AMAN SAI (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The aim of the study was to compare the efficacy of 0.5% levobupivacaine and 0.75% ropivacaine after intrathecal administration in elective lower limb surgeries. Methods: A prospective, randomized, controlled, and double-blind study was conducted on 100 patients undergoing elective lower limb surgeries under subarachnoid block using 0.5% levobupivacaine and 0.75% ropivacaine. Results: Demographic characteristics of both groups are comparable. It is observed the onset of sensory blockade is earlier in ropivacaine group, Grade 4 bromage scale motor blockade onset is shorter in levobupivacaine and most of the parameters are comparable between two groups. Duration of sensory blockade is more in ropivacaine when compared to levobupivacaine. Levobupivacaine is more cardiostable with stable hemodynamic profile compared to ropivacaine. Conclusion: Levobupivacaine is more cardiostable with stable hemodynamic profile compared to ropivacaine.